Analisa dan Perancangan Sistem Informasi Pengolahan Data Pegawai Pada Kantor Satuan Polisi Pamong Praja - Ferry Prasetyo (ISB Atma Luhur, 2014)
Office of Civil Service Police Unit Pangkalpinang formed in order to carry out the duties of government field Enforcing Regulation (Regulation), which is led by a Head of the Office of the Mayor Pangkalpinang jawan held by the Regional Secretary. Office of Civil Service Police Unit Pangkalpinang is located at Jl. Diamond Stone Village Girimaya Pangkalpinang. Office of Civil Service Police Unit Pangkalpinang have some technical areas and sub-sections. Here will be discussed regarding employee data processing system consisting of employee data collection in and out through the process of moving staff, The process of making DP3 (List of Work Implementation Assessment), the process of making a Certificate of Family Allowances To Get Payments (KP4), periodic employee payroll process, the process of recording training and reporting process. All data processing personnel in the Office of Civil Service Police Unit Pangkalpinang relate to the Regional Employment Board and the Department of Revenue, Finance and Asset Management Regional Pangkalpinang.